PROSPEK PENGEMBANGAN KERJASAMA ANTAR DAERAH KABUPATEN/KOTA DI KALIMANTAN TIMUR DALAM PENYELENGGARAAN URUSAN PEMBANGUNAN DAN PELAYANAN MASYARAKAT - Tri Widodo W. Utomo (Jurnal Borneo Administrator, 2006)
The promulgation of extended-decentralization policy has brought about the competition climate among district/city governments in delivering public services. The capacity to accomplish public tasks, however, tends to be insufficient. That’s why, regional-cooperation-based management is believed as the paramount mode to minimize local government’s shortage on the one hand, and to improve public accountability and performance on the other hand. In the East Kalimantan case, the tradition of conducting public affairs through collaborative management seems to be disregarded. Nevertheless, the prospect to intensify regional cooperation is fairly promising. This paper examines the likely development cooperation among three autonomous regions, i.e. Bontang City, East Kutai District, and Kutai Kartanegara District, the Bosanggarong (Bontang, Sangatta, and Tenggarong) Development Forum. The study has been highlighted on three dimension of development: provision of basic infrastructure facilities (public works), environmental management, and garbage / waste-disposal services.  Keywords: Otonomi / desentralisasi, kerjasama antar daerah, pelayanan masyarakat